Soft Regulators, tough judges - Gerrit G.A. de Geest; Guiseppe Dari Mattiacci (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
Judges have a tendency to be more demanding than regulators. In the United States, a majority of the courts has adopted the rule that the unexcused violation of a statutory standard is negligence per se. However, the converse does not hold: compliance with regulation does not relieve the injurer of tort liability. In most European legal systems, the outcome is similar. We use a framework in which, on the one hand, the effects of tort law are undermined by insolvency and evidence problems and, on the other hand, regulation is expensive in terms of monitoring and information gathering. We show that a regulatory standard set below the socially optimal level of care can be sufficient to remove the shortcomings of tort law. In essence, this is because the injurer's cost function may have two local minima that make only major deviations from the socially desirable level of precaution advantageous for the injurer, but not minor violations. This may occur when precaution also or only reduces the magnitude of the harm and under liability for negligence.Thus, minimum regulation can completely restore optimal liability incentives. Conversely, liability reduces the cost of enforcing regulation in two ways: first, enforcing minimum regulation rather than a standard set at the socially optimal level is cheaper because it requires lower monitoring levels; second, tort liability already provides a part of the sanction for sub-optimal behavior, thus allowing for a further reduction in monitoring.Moreover, we show that minimum regulation does not need to be set at a very precise level. On the contrary, any level within a certain range is socially optimal. This allows regulators to further curb their cost by saving on information gathering.We show that an imperfectly working tort system can be fully corrected by minimum regulation in a variety of circumstances (for instance, even if the injurer is unable to compensate for the harm at the optimal level of precaution, and even if the rule in force is strict liability or a cause-in-fact variant of negligence).
Keywords: 330; insolvency; judgment proof problem; disappearing defendant; bankruptcy; regulation